A Multilevel Inverter for Grid-Connected Photovoltaic Systems Optimized by Genetic Algorithm - Boucheriette, Wafa; Moussi, Ammar; Mechgoug, Raihane; Benguesmia, Hani (Engineering, Technology & Applied Science Research, 2023)
This article introduces a grid-connected photovoltaic (PV) source combined with a multi-level inverter. A converter five-level neutral point (NPC) can be used to integrate the PV power into the power grid with minimum harmonic distortions and high power capacity. If the output voltage of the PV generator varies significantly with solar radiation, the output voltage of the ripple must be fixed. For this reason, a regulation loop was used. In this study, we used a classical PI regulator. It is difficult to determine the PI controller transaction values, so Genetic Algorithm was used to optimize the PI controller parameters. The Matlab/Simulink simulation results show the better performance and efficiency of the PI controller optimized by the GA, in comparison to the stand-alone PI controller, regarding stability and accuracy, and the reduction of Total Harmonic Distortions (THD) of the current injected into the grid for any difference in solar radiation.